Prevalence of sensory impairments in home care and long-term care using interRAI data from across Canada - Guthrie, Dawn M.; Williams, Nicole; Jaiswal, Atul; Mick, Paul; O'Rourke, Hannah M.; Pichora-Fuller, M. Kathleen; Wittich, Walter; Sutradhar, Rinku (Scholars Commons @ Laurier, 2022)
Background In the general population, sensory impairments increase markedly with age in adults over 60 years of age. We estimated the prevalence of hearing loss only (HL), vision loss only (VL), and a combined impairment (i.e., dual sensory loss or DSL) in Canadians receiving home care (HC) or long-term care (LTC). Methods Annual cross-sectional analyses were conducted using data collected with one of two interRAI assessments, one used for the HC setting (n = 2,667,199), and one for LTC (n = 1,538,691). Items in the assessments were used to measure three mutually exclusive outcomes: prevalence of VL only, HL only, or DSL. Trends over time for each outcome were examined using the Cochran-Armitage trend test. A negative binomial model was used to quantify the trends over time for each outcome while adjusting for age, sex and province. Results In HC, there was a significant trend in the rate for all three outcomes (p < 0.001), with a small increase (roughly 1%) each year. In HC, HL was the most prevalent sensory loss, with a rate of roughly 25% to 29%, while in LTC, DSL was the most prevalent impairment, at roughly 25% across multiple years of data. In both settings, roughly 60% of the sample was female. Males in both HC and LTC had a higher prevalence of HL compared to females, but the differences were very small (no more than 2% in any given year). The prevalence of HL differed by province after adjusting for year, age and sex. Compared to Ontario, Yukon Territory had a 26% higher rate of HL in HC (relative rate [RR] = 1.26; 95% confidence interval [CI]:1.11, 1.43), but LTC residents in Newfoundland and Labrador had a significantly lower rate of HL (RR: 0.57; CI: 0.43, 0.76).When combined, approximately 60% of LTC residents, or HC clients, had at least one sensory impairment. Conclusions Sensory impairments are highly prevalent in both HC and LTC, with small sex-related differences and some variation across Canadian provinces. The interRAI assessments provide clinicians with valuable information to inform care ...